A utilização dos paradigmas de Drash e Tudor (1993) na condução do desenvolvimento verbal de uma criança de 5 anos - Oliveira, Denise de Lima (2005)
Verbal behavior is operant behavior and therefore is ruled by the laws of reinforcement. Reinforcement contingencies may yield suppression or low frequency of verbal responses. The purpose of this work was: to formulate hypothesis of possible contingencies of reinforcement that could suppress or lower the frequency of verbal responses; to observe family interactions and identify the contingencies that could lower the frequency of verbal responses and raise the frequency of inappropriate behavior; to develop procedures of intervention through parents counseling and to verify possible changes in the frequency of verbal responses emitted by a 5 year-old child. In order to accomplish this purpose, an interview to assess the history of the child and of the parents complaint was carried out; one hour observation sessions in the child s home were done for 7 months; and, at the end of each observation session, parents counseling took place. The purpose of parents counseling was to instruct them to differentially reinforce alternative responses, teach naming, reinforce vocal mands, consequence the emission of verbal responses, alter the frequency of watching TV and playing video game, and perform extinction for inappropriate behavior. The interaction of family members were transcribed and categorized. The results show that the child was exposed to unfavorable contingencies in the beginning of the experiment and in his/her previous life, which had yield suppression and/or low frequency of verbal responses. The instructions given by the researcher seem to have produced changes in the parents behavior and, consequently, in the child s behavior, leading to an increased frequency of verbal responses and a decreased frequency of inappropriate behavior. In addition, the data show that changes in the interactions of all members of the family happened, confirming that verbal behavior is shaped and maintained by reinforcement contingencies.